Analisis Pemangku Kepentingan Destinasi Pariwisata Dieng Plateau Jawa Tengah - Destha T Raharjana; Heddy S Ahimsa-Putra; Djoko Wijono; Hendrie A Kusworo (HOSPITALITI DAN PARIWISATA, 2019)
The existence of stakeholders has an important role for the implementation of the Dieng Plateau tourism policy. This view is quite rational because tourism is an industry that might work if supported by other relevant stakeholders. This is where the strategic tourism stakeholders are, including in order to encourage tourism management of Dieng Plateau as a leading destination in Central Java. The existence of Government Regulation No. 50/2011 concerning RIPPARNAS establishes Dieng tourism area and its surroundings as a national tourism strategic area (KSPN) emphasizing the importance of collaboration among stakeholders in managing destinations. Furthermore, this article was prepared with the aim of analyzing stakeholders who are seen as having interests and influence in the management of tourism in the Dieng Plateau. The analysis is carried out to identify stakeholders, analyze stakeholder involvement, categorize stakeholders, and analyze relationships between stakeholders by looking at aspects of communication, coordination and cooperation (3K). The results of the analysis show that there are five stakeholders including subjects and context setters, ten stakeholders included in the key players group, and thirteen stakeholders belong to the crowds group. Analysis of its involvement, only six stakeholders were seen as having strong involvement in setting policies, providing funding, research or advocacy support, providing technology / training facilities, and conservation / maintenance of infrastructure. In the future, stakeholders involved in managing tourism in the Dieng Plateau need to strengthen structural or non-structural dimensions.